Short-Term Treatment with Silymarin Improved 6-OHDA-Induced Catalepsy and Motor Imbalance in Hemi-Parkisonian Rats - Rasool Haddadi; Shahla Eyvari Brooshghalan; Safar Farajniya; Alireza Mohajjel Nayebi; Hamdolah Sharifi (Tabriz University of Medical Sciences, 2015)
Purpose: Parkinson's disease (PD) is a common neurodegenerative disorder characterized by disabling motor abnormalities, which include tremor, muscle stiffness, paucity of voluntary movements, and postural instability. Silymarin (SM) or milk thistle extract, is known to own antioxidative, anti-apoptotic, anti-inflammatory and neuroprotective effects. In the present study, we investigated the effect of intraperitoneal (i.p) administration of SM, on 6-OHDA-induced motor-impairments (catalepsy and imbalance) in the rats. Methods: Experimental model of PD was induced by unilateral infusion of 6-hydroxydopamine (6-OHDA; 8 μg/2 μl/rat) into the central region of the substantia nigra pars compacta (SNc). Catalepsy and motor coordination were assessed by using of bar test and rotarod respectively. Results: The results showed a significant (p<0.001) increase in catalepsy of 6-OHDA-lesioned rats whereas; in SM (100, 200 and 300 mg/kg, i.p for 5 days) treated hemi-parkinsonian rats catalepsy was decreased markedly (p<0.001). Furthermore, there was a significant (p<0.001) increase in motor-imbalance of 6-OHDA-lesioned rats. SM improved motor coordination significantly (p<0.001) in a dose dependent manner and increased motor balance. Conclusion: In conclusion, we found that short-term treatment with SM could improve 6-OHDA-induced catalepsy and motor imbalance in rats. We suggest that SM can be used as adjunctive therapy along with commonly used anti-parkinsonian drugs. However, further clinical trial studies should be carried out to prove this hypothesis.